Technical improvement in DNA preparation for pulsed-field gel electrophoresis - Thong, Kwai Lin; Lai, K.S.; Goh, Yee Ling (Faculty of Science, University of Malaya, 2003)
We report a rapid pulsed-field gel electrophoresis (PFGE) protocol for subtyping Salmonella isolates. Modifications were made to reduce the number of steps and duration of proteolysis in our original protocol for the preparation of intact, genomic DNA for PFGE analysis. Comparison of PFGE patterns by independent researchers showed that subtyping results using this modified, rapid protocol were highly reproducible.